2007
DOI: 10.1007/bf03325979
|View full text |Cite
|
Sign up to set email alerts
|

Controlling factors of groundwater hydrochemistry in a small island’s aquifer

Abstract: ABSTRACT:Factor analysis was applied to the hydrochemical data set of Manukan Island in order to extract the principal factors corresponding to the different sources of variation in the hydrochemistry. The application of varimax rotation was to ensure the clear definition of the main sources of variation in the hydrochemistry. The geochemical data of dissolved major, minor and trace constituents in the groundwater samples indicates the main processes responsible for the geochemistry evolution. By using Kaiser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 5 publications
0
20
0
4
Order By: Relevance
“…The acidity found in forest wells is usually associated with carbonic acid dissolution, rock weathering and litter decomposition over the forest floor, which yields organic acids. [25][26][27] In fact, Williams et al and Chaves et al studying intact forests in Central Amazonas and Rondônia, respectively, found more acidic pH values (4.7 and 5.2) than those observed in the Urupá basin. 15,16 In addition to the above mentioned factors influencing acidity in groundwater, in rural and urban areas, domestic and industrial sewage disposal and soil alteration through corrective products and fertilizers can also influence pH.…”
Section: Resultsmentioning
confidence: 94%
“…The acidity found in forest wells is usually associated with carbonic acid dissolution, rock weathering and litter decomposition over the forest floor, which yields organic acids. [25][26][27] In fact, Williams et al and Chaves et al studying intact forests in Central Amazonas and Rondônia, respectively, found more acidic pH values (4.7 and 5.2) than those observed in the Urupá basin. 15,16 In addition to the above mentioned factors influencing acidity in groundwater, in rural and urban areas, domestic and industrial sewage disposal and soil alteration through corrective products and fertilizers can also influence pH.…”
Section: Resultsmentioning
confidence: 94%
“…Parameter yang terlampaui oleh semua sampel airtanah adalah parameter magnesium dan BOD. Pengayaan magnesium merupakan ciri-ciri dari pengaruh intrusi airlaut [17,18,19]. Kondisi yang sama ditemukan dalam penelitian sebelumnya yang dilakukan di Pulau Koral Panggang dan Pulau Koral Pramuka.…”
Section: Kondisi Sumberdaya Airtanah DI Pulau Koral Pariunclassified
“…There are also accommodation available with excellent facilities (i.e., 20 unit chalets, a clubhouse, restaurant, souvenirs, diving centers and recreational facilities such as a swimming pool, football field, squash and tennis courts) and good infrastructure support (i.e. water, electricity, desalination plant, sewerage system and even a solar powered public telephone) (Abdullah et al, 2002;Aris et al, 2007;Aris et al, 2009).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Seawater intrusion becomes a threat when the interface moves far enough inland to render drinking water wells salty and unusable. Intensive exploitation of groundwater and wells shutdown in Manukan Island's aquifer is indicating that the natural equilibrium between fresh and seawater has been disturbed (Aris et al, 2007;. …”
Section: Site Descriptionmentioning
confidence: 99%